Formal aspects of component software : 15th International Conference, FACS 2018, Pohang, South Korea, October 10-12, 2018, Proceedings /: 15th International Conference, FACS 2018, Pohang, South Korea, October 10-12, 2018, Proceedings. (2018) - Unknown
No abstract available